(untitled) (World Bulletin of Social Sciences, 2023)
In this article, the issue of the role of artistic image tools in the reflection of spiritual and moral problems in Erkin Azam’s stories "Yozhvchi" and "Aralashkurgan" is studied, and the artistic features of both stories of the writer, in particular, special attention is paid to the issues of imagery and representation of components in it. Paying attention to the fact that the reasons for the origin of fraud, bribery, ambition, greed and stratification among the many evils in today’s society, and the loss of kindness due to them, are clearly expressed due to the skill of the writer. directed